The interaction between dynamic recrystallization and twinning during the hot compression in a novel nickel-based superalloy - Xingyun Fan; Lingxiang Zhong; Yanzhuo Liu; Jianmin Cui; Hongqiang Du; Yongsheng Wei; Yingnan Shi; Xinmei Hou; Jinhui Wang; Peipeng Jin (Journal of Materials Research and Technology)
Twinning and dynamic recrystallization (DRX) have been widely reported as important mechanisms for accommodating plastic deformation in nickel-based superalloys. However, the interaction mechanisms between twinning and DRX has rarely been reported. The thermomechanical deformation behavior of a novel extruded nickel-based powder superalloy (NNS) was investigated. Isothermal hot compression tests were conducted to obtain true stress-strain curves and the influence of deformation parameters on the microstructural evolution of the NNS alloy was analyzed. The results showed that the alloy underwent extensive twinning to accommodate plastic deformation. These deformation twins (DTs) were nucleated via the double-cross slip model at low temperatures and high strain rates. Additionally, it was found that the twins on the γ′ are nucleated by the interaction of two a/2[110] dislocations and the interaction produce two partial dislocations (a/3[21 1‾] and a/3[1 2‾ 1]), which cut adjacent (111) planes and thus promoted twin nucleation. The DTs promoted DRX nucleation. The growth of DTs suppressed the growth of the DRXed grains and thus refined the grain.